Quasiparticle spectrum of d-wave superconductors in the mixed state - Marinelli, L; Halperin, B; Simon, S (2000)
The quasiparticle spectrum of a two-dimensional d-wave superconductor in the mixed state, Hc1 ≪H≪Hc2, is studied both analytically and numerically using the linearized Bogoliubov-de Gennes equation. We consider various values of the "anisotropy ratio" υF/υΔ for the quasiparticle velocities at the Dirac points, and we examine the implications of symmetry. For a Bravais lattice of vortices, we find there is always an isolated energy zero (Dirac point) at the center of the Brillouin zone, but for a non-Bravais lattice with two vortices per unit cell there is generally an energy gap. In both of these cases, the density of states should vanish at zero energy, in contrast with the semiclassical prediction of a constant density of states, though the latter may hold down to very low energies for large anisotropy ratios. This result is closely related to the particle-hole symmetry of the band structures in lattices with two vortices per unit cell. More complicated non-Bravais vortex lattice configurations with at least four vortices per unit cell can break the particle-hole symmetry of the linearized energy spectrum, and lead to a finite density of states at zero energy. ©2000 The American Physical Society.